Biological Mechanisms Linking Alzheimer’s Disease and Type-2 Diabetes Mellitus - Mushtaq, Gohar; A. Khan, Jalaluddin; A. Kamal, Mohammad (CNS & Neurological Disorders - Drug Targets, 2014)
The emerging data suggest that type 2 diabetes mellitus (T2DM) can contribute significantly to the onset or progression of Alzheimer’s disease (AD) either directly or as a cofactor. Various in vitro and in vivo animal and human clinical studies have provided evidence that T2DM is a major risk factor in the pathology of AD and the two diseases share common biological mechanisms at the molecular level. The biological mechanisms that are common in the pathology of both T2DM and AD include insulin resistance, impaired glucose metabolism, β-amyloid formation, oxidative stress, and the presence of advanced glycation end products. With better understanding of the degree of association between AD and T2DM and the underlying molecular mechanisms explaining this relationship, it is hoped that researchers will be able to develop effective therapeutic interventions to treat or control T2DM and, as a consequence, delay the onset or progression of AD.
Keywords: oxidative stress